Implementation of Government Performance Accountability System (SAKIP) in Indonesian Local Government (Case of Regional Development Planning Board of Sukabumi Regency) - Tomi Setianto; Sinta Ningrum; Didin Muhafidin (Jurnal Manajemen Pelayanan Publik, 2021)
The use of performance measurement system in the public sector (PMS) has become a panacea in addressing an inefficient bureaucracy that fails to meet the citizen satisfaction by its lethargic service delivery. It has introduced a way for public managers to better generate outcome policy into a concrete-measurable actions. While many countries already demonstrates the benefit of using the system, Indonesia remain struggle in implementing the ideal of performance management particularly in the context of local government that usually lacking of adequate capacity and sources. Despite the continuous support by central government, the diverse of socio-environmental context hinder local government to fully implements of SAKIP. This paper sought to portray the implementation and challenges that is faced by one local government agencies in Sukabumi, West Java Indonesia in implementing Indonesian public performance management system (SAKIP). This paper is using qualitative approach by conducting structured interview to key informants. The results showed that organizational variables have been able to accommodate the implementation of SAKIP policy through units formed specifically in organizational structure and governance regulations, organizational interpretation variables are still necessary to improve the dissemination of policy information to all levels of employees, application variables where the implementation of policies are still experiencing constraints, especially in planning and evaluation, as well as a lack of specific strategies in improving organizational performance. This paper reinforces the results of previous studies related with performance management system in Indonesian local government that its implementation has not been yet showing their best result.